PERAN PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE DALAM MEMEDIASI PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI EMPRIS PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Ahmad Sahri Romadon; Heru Sulistiyo; Sam’ani Sam’ani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
This research is about the value of property and real estate companies in Indonesia Stock Exchange 2013 to 2016. The purpose is to analyze Profitability and Good Corporate Governance in mediating the influence of Capital Structure and Corporate Growth on company value. Methods of data analysis using multiple regression and test to test the hypothesis sobel. Population in this research is property and real estate company listed in Indonesia Stock Exchange 2013 until 2016. Samples in this research selected through purposive sampling, so that obtained by sample as many as 80 companies. The result shows that capital structure has a significant negative effect on profitability, company growth has a significant positive effect on profitability. Capital structure has a significant positive effect on Good Corporate Governance, Corporate Growth has negative effect is not significant to Good Corporate Governance. Capital structure has a significant positive effect on firm value, company growth has negative effect not significant to firm value. Profitability has a significant positive effect on corporate value and Good Corporate Governance negatively influence not significant to company value. Profitability mediates negatively the influence of capital structure on firm value and positively positive significant growth of the firm against firm value. Good Corporate Governance does not mediate the influence of capital structure and firm growth on firm value